Makna Dibalik Tambur Peh Cun dalam Masyarakat Tionghoa Benteng: Sebuah Analisis Kultural Berdasarkan Teori Yin-Yang - Michael Hari Sasongko; Dody Candra Harwanto; Alfa Kristanto (Program Studi Pendidikan Musik FBS UNP, 2022)
Historically, the Benteng Chinese community was a marginalized community. Its existence in Indonesia cannot be separated from discrimination caused by political distortions, since the Dutch occupation, the Old Order, the New Order, until the Reformation Order. This results in poverty in various aspects. However, since the revocation of Presidential Instruction No. 14/167 revoked and replaced with Presidential Decree No. 6/2000, this community is free to express its cultural forms. This is evidenced by the existence of the Peh Cun drumming tradition in the Dragon Boat Festival. This study aims to reveal the meaning behind the Tambur Peh Cun tradition through the theory of Yin Yang and try to obtain a new theory about the essence of Peh Cun. That means this research uses a qualitative. Based on this analysis, it is revealed that Peh Cun or boat racing is not merely entertainment, a form of tourism, or ordinary art, but has an ideological meaning, which contains hopes and aspirations for equal rights and obligations as Indonesian citizens in general and treatment fair.